Pengaruh Mutu Pelayanan Obat IFRS Terhadap Kepercayaan Pasien Umum Rawat Jalan dan Dampaknya Pada Peningkatan Brand Awarness Dan Brand Image Rumah Sakit Cinta Kasih Tzu Chi Cengkareng - Endang Mariyanti; Sri Widyastuti; Sahat Saragi (Universitas Pahlawan Tuanku Tambusai, 2023)
This research was motivated by a decrease in the number of prescription sheets with the number of visits from 2016 to 2020 and patient dissatisfaction in the form of complaints at this hospital. The purpose of this study was to determine the patient's response to brand awareness and brand image regarding the decision to use the outpatient unit at Cinta Kasih Tzu Chi Hospital. This type of research is descriptive using a quantitative approach. The population in this study were general patients who redeemed drugs through a doctor's prescription at the IFRS outpatient unit of the Cinta Kasih Tzu Chi Hospital in Cengkareng with a total sample of 365 general patients. The data was processed using the statistical test of Structural Equation Modeling (SEM) which was run through AMOS 24. The results showed that the quality of drug services had a positive and significant effect on trust, trust had a positive and significant effect on brand awareness, and trust had no positive effect on brand image. where p value = 0.301 and brand awareness has a positive and significant influence on brand image.